SOLIDARITAS ANTAR MAHASISWI YANG TINGGAL DI RUSUNAWA UNIVERSITAS TANJUNGPURA PONTIANAK - Dian Herlina; Yohanes Bahari; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe title of this article is “Solidarity Between Student Who Lived In Rusunawa University of Tanjungpura”. The general problem of this research is “how solidarity among student from the rusunawa of University of Tanjungpura?”. Based on the general problem is then presented into sub problem is then presented into sub problems as follows: 1. How the mechanical soidarity among student from the rusunawa of university Tanjungpura? 2. How is organic solidarity among student from the rusunawa of university Tanjungpura? Based on observations and interviews of researchers in the field in general 1. Mchanical solidarity between student who live in subsidized apartments already well established, it appears they help each other in many ways, one of them at a time of their friends who are sick , they immeediately helped. 2. Organic solidarity among student who live in subssidized apartments university of Tanjungpura, has not been well established, most of them do not carry out activities that have been given the rusunawa they have no interest to the interdependence that can form organic solidarity.Keywords: Solidarity, Student, Occupants Rusunawa